Gaya Belajar Siswa Bimbingan Belajar Luar Sekolah: Studi Kasus di Kota Bandung - Arditya Prayogi (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2025)
This article aims to provide a descriptive overview of the characteristics of the learning styles of out-of-school tutoring students, and how these characteristics contribute to educational success. The study was conducted using a descriptive-qualitative method with a case study approach on tutoring students in the city of Bandung. Data were collected through observation and interviews, then analyzed systematically. The results of the study indicate that tutoring students have diverse learning styles, with a dominance of auditory learning styles because learning in tutoring is often delivered orally. In addition, tutoring students tend to have high motivation, diverse academic backgrounds, and specific learning needs. The implication of this finding is the importance of a deep understanding of student learning characteristics by tutoring institutions and tutors. Thus, tutoring institutions can develop learning strategies that are inclusive, effective, and support the development of student potential holistically.